Effect of Plastrum Testudinis Extracts on the Proliferation and Osteogenic Differentiation of rBMSCs by Regulating p38 MAPK-Related Genes. (7th March 2019) - Shang, Qi; Yu, Xiang; Ren, Hui; Shen, Gengyang; Zhao, Wenhua; Zhang, Zhida; Huang, Jinjing; Yu, Peiyuan; Liang, De; Tang, Jingjing; Jiang, Xiaobing
Abstract : Extracts from plastrum testudinis (PTE) are active compounds that have been used to treat bone diseases in traditional Chinese medicine for thousands of years. In previous studies, we demonstrated their effects on glucocorticoid-induced osteoporosis both in vivo and in vitro . However, the mechanisms by which PTE regulates the osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (rBMSCs) in vitro remain poorly understood. In this study, rBMSCs were treated with medium (CON), PTE, osteogenic induction (OI), and a combination of PTE and OI (PTE+OI) over a 21-day period. We found that PTE significantly promoted rBMSCs osteogenic differentiation and mineralisation after 21 days of culturing. Moreover, PTE+OI further enhanced the differentiation and mineralisation process. PTE upregulated STE20, IGF1R, and p38 MAPK mRNA expression and downregulated TRAF6 mRNA expression. The extracts inhibited TRAF6 protein expression and promoted STE20, IGF1R, and phosphorylated p38 MAPK protein expression. Our results imply that PTE promotes the proliferation and osteogenic differentiation of rBMSCs by upregulating p38 MAPK, STE20, and IGF1R and downregulating TRAF6 expression, which may provide experimental evidence of the potential of PTE in the treatment of osteoporosis.